Food Product Development Lab Manual - Prusa, Ken; Gilbert, Kate (Open textbook library., 2021)
A practical how-to illustrating the process of developing a new food product from ideation and formulation to processing and lastly commercialization. This book highlights the overall process and gives instructions for each of the steps along the way.